1999
DOI: 10.1128/aac.43.5.1144
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Microencapsulated Rifampin in Mycobacterium tuberculosis -Infected Mice

Abstract: Rifampin is a first-line drug useful in the treatment of tuberculosis. By using biocompatible polymeric excipients of lactide and glycolide copolymers, two microsphere formulations were developed for targeted and sustained delivery of rifampin, with minimal dosing. A small-microsphere formulation, with demonstrated ability to inhibit intracellularly replicating Mycobacterium tuberculosisH37Rv, was tested along with a large-microsphere formulation in an infected mouse model. Results revealed that by using a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Mechanistic insights into persistence can find better targets for novel drugs to shorten the tuberculosis treatment duration. In this study, we found that the glutamine can sensitize M. smegmatis to rifampicin-mediated killing ( Figures 1A,B ) ( di Mauro et al, 1969 ; Quenelle et al, 1999 ; Campbell et al, 2001 ), consistent with previous publications showing that high concentration arginine can synergize with gentamicin against E. coli ( Recht and Kolter, 2001 ; Lebeaux et al, 2014 ; Shan et al, 2015 ). Notably, prolonged starvation can enhance the tolerance to rifampicin though the addition of glutamine increased the activity of rifampicin (Supplementary Figure 2 ).…”
Section: Discussionsupporting
confidence: 92%
“…Mechanistic insights into persistence can find better targets for novel drugs to shorten the tuberculosis treatment duration. In this study, we found that the glutamine can sensitize M. smegmatis to rifampicin-mediated killing ( Figures 1A,B ) ( di Mauro et al, 1969 ; Quenelle et al, 1999 ; Campbell et al, 2001 ), consistent with previous publications showing that high concentration arginine can synergize with gentamicin against E. coli ( Recht and Kolter, 2001 ; Lebeaux et al, 2014 ; Shan et al, 2015 ). Notably, prolonged starvation can enhance the tolerance to rifampicin though the addition of glutamine increased the activity of rifampicin (Supplementary Figure 2 ).…”
Section: Discussionsupporting
confidence: 92%
“…More infiltration and accumulation of lymphocytes were observed in the non-immunized placebo control mice (Figure 3B,C). Next, we investigated whether treatment with C 4 .T 4 agonists potentiate the efficacy of anti-TB drugs even at a lower dose than the recommended concentration [50]. Interestingly, we observed that treatment of mice with C 4 .T 4 in combination with RIF considerably (p < 0.001) boosted the killing efficacy of the drug, when compared to the drug alone (Figure 3D).…”
Section: Clec4e and Tlr4 Agonists Enhanced Macrophage Bactericidal Activitymentioning
confidence: 95%
“…doses of small microspheres with an oral dosing of INH for 25 days. While RIF loaded microspheres showed 1.23 log 10 reduction in CFU, combination with INH resulted in nearly complete elimination of CFU from the lungs and spleen [9,[56][57][58].…”
Section: Microparticulate Delivery Systems (Mds)mentioning
confidence: 96%